Valorization of horse manure conversion to magnetic carbon nanofiber for dye adsorption by hydrothermal treatment coupled with carbonization - Napat Kaewtrakulchai; Sirayu Chanpee; Warit Pasee; Ampol Putta; Sutee Chutipaijit; Malinee Kaewpanha; Tawat Suriwong; Pramote Puengjinda; Gasidit Panomsuwan; Masayoshi Fuji; Apiluck Eiad-ua (My University, 2023)
Pollution of water resources has recently increased as a result of expanded industrial activity. Recycling waste biomass into bio-adsorbent material offers a cheap, easy, and eco-friendly solution. In this study, magnetic carbon nanofibers (MCNF) with a highly porous structure were developed from magnetite-preloaded horse manure by hydrothermal treatment followed by carbonization using different ratios of iron (III) nitrate and iron oxide as magnetic precursors. The produced MCNF had a very porous structure with specific surface area of 435.31 m2/g and high carbon content. The magnetic characteristics of MCNF promoted by the presence of iron oxide species. The saturated magnetization of MCNF obtained from a 5:5 ratio of the magnetic precursors (iron (III) nitrate: iron oxide) was 2.48 emu/g. Synthesized MCNF was applied as a bio-adsorbent for methylene blue (MB) removal from aqueous solution, with results showing excellent dye adsorption of 92–99 %. MB adsorption was facilitated by pore filling, electrostatic contact, hydrogen bonding, and ion complexation. Experimental results indicated that the Freundlich isotherm and pseudo-second-order kinetic models concurred with the observed MB adsorption data, suggesting that the adsorption mechanism involved multilayered micropore interactions between magnetite and MB chemisorption. The resulting magnetic adsorbent was successfully removed from the aqueous solution by physical separation. Findings indicated that horse manure-derived MCNF could be used as an efficient bio-adsorbent to remove organic contaminants in wastewater.
Keywords: Hydrothermal Carbonization; Carbon fibers; Adsorption and biosorption for pollutant removal